A brief component analysis of potential treatment packages in an outpatient clinic setting with young children. - Millard, T (1993)
The purpose of this study was to develop outpatient clinic assessments that allowed us to assess multiple treatment variables, produce relatively quick effects, and isolate active treatment components. Assessment began by evaluating a treatment package consisting of antecedent and consequence variables followed by a component analysis to determine the separate effects of the treatment variables. Three examples of the findings are presented.